Perbedaan Hasil Tangkapan Pancing Ulur Berdasarkan Warna Umpan Yang Digunakan Di Perairan Pulau Maginti Kabupaten Muna Barat - Yusril Yusril; Hasnia Arami; Syamsul Kamri; Muslim Tadjuddah; Abdullah Abdullah (Universitas Halu Oleo, 2023)
Hand line is a simple fishing gear where this fishing gear consists of a capstan, fishing line, swivel, artificial bait and weight. The operation of this fishing gear is very simple where the operation can be done by an angler and does not require much operational cost. The technique of operation is by lowering the fishing rod paired with bait to the bottom and then pulled back after the fish is caught in the fishing rod is raised on the boat. The purpose of this study was to determine the composition of the types and sizes of fish caught based on the color of the bait used (white, green and blue), and to determine the effect of using different bait colors on the catch. This research was conducted in January and February 2023 in the waters of Maginti Island, West Muna Regency. This research used experimental fishing method, in which the researcher participated in the operation of handline fishing for 20 trips. The results of the study found that the total catch with white bait caught was 173 individuals of 7 species of fish, green bait 88 individuals of 4 species of fish and blue bait 40 individuals of 4 species of fish. In the three types of bait color yellow mackerel (Selaroides leptolepis) is the most dominant fish caught. The size distribution is in the class interval of 9.1-19 cm TL. Based on the results of the ANOVA test, it shows that the use of different bait colors has no significant effect on the number of catches